Peranan Filsafat Ilmu Bimbingan dan Konseling dalam Kompetensi Konselor Multikultural di Indonesia - Hastiani Hastiani; nurul rahmi (JURNAL KONSELING GUSJIGANG, 2021)
Philosophy of science is the founfation of implementation for guidance and counseling services, leading the councelor to the concept about substances and human roles in counseling process. Philosophy of science as the Mother of Science becomes a frame work for councelor in providing assistence process to individual. The important role of philosophy of science as an insight which used by the councelor in his insight  for doing  therapheutics, using critical thinking skill to know about the human condition. Viewing the very diverse of Indonesian society such as ethnicities, religions, values, and perspectives. The condition of diversity becomes a challenge for current guidance and counseling and future expectations in multicultural counseling. The competence of councelor in muliticultural counseling can not be separated in the study of philosophy of guidance and counseling, because that is the foundation for the implementation of multicultural guidance and counseling services in Indonesia